Place, Craft and Neurodiversity Re-imagining Potential through Education at Ruskin Mill - Gordon, Aonghus (Taylor & Francis, 2024)
For over four decades, Ruskin Mill Trust has worked with young people with special educational needs and behavioural issues who learn traditional crafts and organic farming as part of an integrated curriculum of therapeutic education, overcoming barriers to learning and re-engaging with the wider world. This accessible and inspiring book showcases how an appreciation of place, traditional crafts, farming and transformative education offers a wider route to human well-being for all. The authors outline the different fields of the "Practical Skills Therapeutic Education" method, which includes developing practical skills, learning the ecology of the farm and understanding therapeutic education, holistic care, health and self-leadership. Taking the reader on a tour of Ruskin Mill's many extraordinary provisions across Britain, and going deeper in conversation with its founder, Aonghus Gordon, this book is an outstanding story of creative thinking in an age of narrow focus on classrooms and written examinations, presenting a transformative perspective on education and care. Being grounded in work supporting young people with complex additional needs, it provides a rare insight into the work of one of the world's leading charities working with neurodiversity. With its non-specialist language, Place, Craft and Neurodiversity offers ideas and resources for work in different areas of education and therapy. It will inspire parents, educators and care workers around the globe.